Insights into Antibody-Mediated Alphavirus Immunity and Vaccine Development Landscape - Torres-Ruesta, Anthony (Microorganisms, 2021)
Alphaviruses are mosquito-borne pathogens distributed worldwide in tropical and temperate areas causing a wide range of symptoms ranging from inflammatory arthritis-like manifestations to the induction of encephalitis in humans. Historically, large outbreaks in susceptible populations have been recorded followed by the development of protective long-lasting antibody responses suggesting a potential advantageous role for a vaccine. Although the current understanding of alphavirus antibody-mediated immunity has been mainly gathered in natural and experimental settings of chikungunya virus (CHIKV) infection, little is known about the humoral responses triggered by other emerging alphaviruses. This knowledge is needed to improve serology-based diagnostic tests and the development of highly effective cross-protective vaccines. Here, we review the role of antibody-mediated immunity upon arthritogenic and neurotropic alphavirus infections, and the current research efforts for the development of vaccines as a tool to control future alphavirus outbreaks.